2011
DOI: 10.1044/1092-4388(2010/10-0097)
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Sexual Dimorphism of the Oral and Pharyngeal Portions of the Vocal Tract: An Imaging Study

Abstract: Purpose-The anatomic origin for prepubertal vowel acoustic differences between males and females remains unknown. The purpose of this study is to examine developmental sex differences in vocal tract (VT) length and its oral and pharyngeal portions.Method-Nine VT variables were measured from 605 imaging studies (MRI and CT) between birth and 19 years. Given sex differences in growth rate ), assessment of sex differences was done using a localized comparison window of 60 months. Analysis entailed applying this c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
56
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 50 publications
7
56
0
Order By: Relevance
“…Avery & Liss, 1996; Fuchs & Toda, 2010) that affect front cavity size. Given the minimal anatomical differences observed by Vorperian et al (2011) for boys vs. girls in the age range 10–14;11 years, a sociophonetic explanation appears to account best for the current data.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Avery & Liss, 1996; Fuchs & Toda, 2010) that affect front cavity size. Given the minimal anatomical differences observed by Vorperian et al (2011) for boys vs. girls in the age range 10–14;11 years, a sociophonetic explanation appears to account best for the current data.…”
Section: Discussionmentioning
confidence: 58%
“…However, Pentz et al (1979) did not find gender differences in spectral peak frequencies for 8.5–11.3-year-olds. The anatomical data of Vorperian et al (2011) suggest that gender differences in young adolescents (ages comparable to those used here) are restricted to nasopharynx size, which should not affect the resonant frequencies of fricatives in the oral cavity; however, as with adults, gender differences in adolescents could arise from any variations in articulatory postures that affect front cavity length. Thus, we evaluated whether our proposed measures showed gender differences.…”
Section: Temporal Context and Speaker Effects In /S/mentioning
confidence: 56%
See 1 more Smart Citation
“…Vorperian et al [7,16] have shown gender differences in growth rates of some aspects of the vocal tract in children of the age range studied here. Goals for future studies will include confirming present findings in a larger sample of female children, and conducting a parallel investigation of vocal tract area growth in male children.…”
Section: Discussionmentioning
confidence: 65%
“…The decision to study one sex was based on the findings of Vorperian et al [16] that there are prepubertal differences in vocal tract growth rates in boys and girls. The decision to study girls was a random choice.…”
Section: Methodsmentioning
confidence: 99%